Obtenção e caracterização de nanocompósitos de poli(cloreto de vinila): plastisol com argila - Bettio, Paola Pedroza Serpa de Biasi (2011)
This project aims to study the effect of adding nanoparticles in the plastisol of poly(vinyl chloride) microsuspension. The influence of two different types of nanoclay, sodium montmorillonite and organophilic montmorillonite modified with quaternary ammonium salt was evaluated, considering both the method of exfoliation of the clay and the influence of concentration. The nanoclay at a concentration of 2.5, 5 or 10 phr, was previously exfoliated in plasticizer, under the action of shear and temperature in kaule mixer. Three plasticizers were used, Diisobutyl phthalate, Diisononyl phthalate and ester polyglycolic. Experiments without the prior exfoliating clay, were also performed for validation of its influence. The plastisol was obtained by mixing the nanoclay with PVC, diisononyl phthalate plasticizer and other additives in planetary mixer. The focus of the study will be not only to investigate the influence of nanoparticles on the improvement of rheological properties, but the influence on the mechanical properties, expanding the application of this resin. As the resin obtained will be attending the main application market, the analysis will focus on characterization for this particular application. Data analysis was performed with the aid of statistical method. It was possible to affirm that type of clay and also its concentration have influence on the viscosity. The prior exfoliation of the clay was not proved to be effective. It was possible to affirm that type and concentration also have significant influence on the opacity of the spread coating. In relation to thermal stability, it was possible to observe reduction in the nanocomposites containing organophilic modified nanoclay. In relation to the mechanical proprieties, it was possible to affirm that only the concentration of the clay was significant to the result, as its increase resulted in a decrease of these properties, with the exception of the Young modulus.